MGTX extension study longitudinally favors early thymectomy in non-thymomatous young-adult patients with AChR antibody-positive myasthenia gravis - Akaishi, Tetsuya; Motomura, Masakatsu; Aoki, Masashi; Utsugisawa, Kimiaki (Annals of Translational Medicine, 2019)
MG is an autoimmune neuromuscular disease that presents weakness of the skeletal muscles. The disease is caused by disturbed neuromuscular transmission mediated by autoantibodies (Ab) against acetylcholine receptors (AChR) or other proteins, such as muscle-specific receptor tyrosine kinase (MuSK) (1). Disturbance of synaptic proteins results in fluctuating muscle weakness with easy fatigability.